Hungarian noun phrase extraction using rule-based and hybrid methods - Recski, Gábor (Acta Cybernetica, 2014)
We implement and revise Kornai's grammar of Hungarian NPs [11] to create a parser that identifies noun phrases in Hungarian text. After making several practical amendments to our morphological annotation system of choice, we proceed to formulate rules to account for some specific phenomena of the Hungarian language not covered by the original rule system. Although the performance of the final parser is still inferior to state-of-the-art machine learning methods, we use its output successfully to improve the performance of one such system.